A New Genus of Highly Specialized Ants in Cretaceous Burmese Amber (Hymenoptera: Formicidae) - Barden, Phillip; Grimaldi, David (Zootaxa, 2013)
A new genus of ants, Zigrasimecia Barden and Grimaldi, is described for a new and uniquely specialized species, Z. ton-sora Barden and Grimaldi n.sp., preserved in Cretaceous amber from Myanmar. The amber is radiometrically dated at 99 myo. Zigrasimecia is closely related to another basal genus of ants known only in Burmese and French Cretaceous amber, Sphecomyrmodes Engel and Grimaldi, based in part on the shared possession of a comb of pegs on the clypeal margin, as well as mandible structure. Highly specialized features of Zigrasimecia include extensive development of the clypeal comb, a thick brush of setae on the oral surface of the mandibles and on the labrum, and a head that is broad, flattened, and which bears a crown of blackened, rugose cuticle. Mouthparts are hypothesized to have functioned in a unique man-ner, showing no clear signs of dentition representative of “chewing” or otherwise processing solid food. Although all ants in Burmese amber are basal, stem-group taxa, there is an unexpected diversity of mouthpart morphologies and probable feeding modes.